Strategic Management in Islamic Education for 21st Century Skills Development - Siti Nafisah; Sunarto Sunarto; Nurul Asma Mazlan (Universitas Negeri Semarang, 2025)
Background - Islamic-based educational institutions increasingly face the dual challenge of equipping students with essential 21st-century competencies while upholding religious and cultural values. Purpose - This study analyzes the strategic management responses of MTs Sadamiyah Jepara, an Islamic-based secondary school, to these contemporary demands. Method/approach - Employing a qualitative case study design, data were gathered through semi-structured interviews, classroom observations, and document analysis. Data credibility was ensured through triangulation, and analysis followed the interactive Miles and Huberman model. Findings - The findings reveal that the school's strategies for fostering 21st-century skills are primarily implemented through two approaches: (1) adopting student-centered learning models that promote problem-solving, creativity, and collaboration via project-based and team-oriented activities; and (2) integrating digital technologies to enhance students’ digital literacy and adaptability. Nonetheless, significant challenges persist, notably in limited technological infrastructure, the ongoing need for teacher professional development, and aligning curricula with evolving skill requirements. Conclusions - The study concludes that Islamic-based schools can play a pivotal role in 21st-century education by synergizing faith-based values with innovative management and instructional practices. Novelty/Originality/Value - This research contributes to the literature by demonstrating how faith-based educational institutions can adapt to global educational standards while maintaining their distinctive religious identity.